Response of mice connective tissue to intracanal dressings containing chlorhexidine - Swerts Pereira, Maristela Soares; Faria, Gisele [UNESP]; Bezerra da Silva, Lea Assed; Tanomaru-Filho, Mario; Kuga, Milton Carlos [UNESP]; Rossi, Marcos A. (Wiley-Blackwell, 2012)
Substances containing chlorhexidine (CHX) have been studied as intracanal medicaments. The aim of the present study was to characterize the response of mouse subcutaneous connective tissue to CHX-containing medications by conventional optical microscopy. The tissue response was evaluated by implanting polyethylene tubes containing one of the substances evaluated: Calen paste + 0.5% CHX, Calen + 2% CHX, 2% CHX gel, and Calen paste (control). After experimental periods of 7, 21, and 63 days, the implants (n = 10) were removed along with the subcutaneous connective tissue. Tissue samples were subjected to histological processing, and sections were stained with hematoxylin and eosin. Qualitative and quantitative analyses of the number of inflammatory cells, blood vessels, and vascularized areas were performed. Results were analyzed by ANOVA and Tukey tests with the significance level set at 5%. We concluded that Calen + 0.5% CHX led to reparative tissue response in contrast with Calen + 2% CHX and 2% CHX gel, which induced persistent inflammatory response, pointing to the aggressive nature of this mixture. When Calen + 2% CHX and 2% CHX gel were compared, the latter induced more intense inflammatory response. Microsc. Res. Tech., 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: biocompatibility; calcium hydroxide; endodontics